1984
DOI: 10.1172/jci111459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute changes of bile acid pool composition on biliary lipid secretion.

Abstract: A s bstract. To elucidate the mechanism responsible for the bile acid-induced changes of biliary lipid secretion, we evaluated bile flow and biliary output of bile acids, cholesterol, phospholipids, and alkaline phosphatase activity in seven cholecystectomized subjects with a balloon occludable T-tube during two experimental periods: (a) depletion of the endogenous bile acid pool and (b) replacement ofthe pool by means ofduodenal infusion with individual bile acids, such as deoxycholic (DCA), chenodeoxycholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 45 publications
5
44
0
Order By: Relevance
“…This observation is consistent with the finding of Carulli et al [25] and Loria et al [26] that biliary secretion of alkaline phosphatase, a bile canalicular membrane constituent, is proportional to the detergent capacity of the administered bile acid in man.…”
Section: Biliary Lipid Couplingsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with the finding of Carulli et al [25] and Loria et al [26] that biliary secretion of alkaline phosphatase, a bile canalicular membrane constituent, is proportional to the detergent capacity of the administered bile acid in man.…”
Section: Biliary Lipid Couplingsupporting
confidence: 92%
“…Bile acid/cholesterol coupling was also increased during cholic acid administration by comparison with results obtained during the bile acid pool depletion phase. The effects of acute changes in bile acid pool composition on biliary lipid coupling have been studied more systematically by Carulli et al [25,26] using a technique similar to that of Schersten et al These authors have confirmed the so-called 'Schersten effect', and reported a progressive decrease in both bile acid/cholesterol and bile acid/phospholipid coupling according to the pattern deoxycholic > CDCA > cholic > UDCA > ursocholic acid (Fig. 2).…”
Section: Biliary Lipid Couplingmentioning
confidence: 97%
“…In two of these studies, the increase in biliary cholesterol was related to either a decrease in CDCA or increase in CA (59,60). In the third, the change in secretion was mainly due to an increase in DCA (61).…”
Section: Resultsmentioning
confidence: 94%
“…The failure of Premarin to alter cholesterol synthesis by mononuclear leukocytes may reflect a true lack of effect of estrogen on cholesterol synthesis, the low potency of Premarin, or less likely, differences in the response of various cell types. (59)(60)(61). In two of these studies, the increase in biliary cholesterol was related to either a decrease in CDCA or increase in CA (59,60).…”
Section: Resultsmentioning
confidence: 99%
“…In man, most (16,17,19) but not all (34) of the available evidence supports a role for deoxycholic acid as feedback inhibitor. It has also been suggested that this bile acid is instrumental not only in regulating bile acid pool sizes but also in affecting biliary cholesterol saturation (46)(47)(48)(49). This may well have a bearing on cholesterol gallstone disease, since in some studies there was a relationship between deoxycholic acid and cholesterol in bile (50).…”
Section: Methodsmentioning
confidence: 99%